Spin‐thermoelectric voltage in longitudinal SSE elements incorporating LPE YIG films and polycrystalline YIG slabs with an ultrathin Pt layer. Issue 3 (6th August 2019) - Imamura, Masaaki; Asada, Hironori; Tashima, Daisuke; Kitagawa, Jiro
Abstract: A spin‐thermoelectric (STE) voltage is generated when a temperature gradient ∇ T is applied to an element having a thin Pt layer coated on a magnetic substance. In this study, yttrium iron garnet (YIG) ferrimagnetic films prepared by liquid phase epitaxy (LPE) were tested as magnetic insulators. In addition, polycrystalline YIG slabs were tested to compare the STE voltages of film and slab samples. In a Pt coating and YIG film bilayer structure made by an ultrathin Pt layer of 1‐4 nm thickness and an LPE film of approximately 10 µm thickness, a large STE voltage of 600 µV was observed at a probe distance of 5 mm with a temperature difference ∆ T of 30 K. On the other hand, the STE voltage of a Pt layer and YIG slab bilayer structure was 340 µV, which is roughly half of that of the Pt/YIG‐film element. The cause of the large voltage observed experimentally for the longitudinal spin Seebeck effect element incorporating an LPE YIG film was discussed mainly from the viewpoint of the Pt layer resistivity and the effects of YIG specimen surface conditions on crystallinity and the magnetization process.